Corneal bioprinting utilizing collagen‐based bioinks and primary human keratocytes. Issue 9 (29th April 2019) - Duarte Campos, Daniela F.; Rohde, Malena; Ross, Mitchell; Anvari, Parham; Blaeser, Andreas; Vogt, Michael; Panfil, Claudia; Yam, Gary Hin‐Fai; Mehta, Jodhbir S.; Fischer, Horst; Walter, Peter; Fuest, Matthias
Abstract: Corneal transplantation is the treatment of choice for patients with advanced corneal diseases. However, the outcome may be affected by graft rejection, high associated costs, surgical expertise, and most importantly the worldwide donor shortage. In recent years, bioprinting has emerged as an alternative method for fabricating tissue equivalents using autologous cells with architecture resembling the native tissue. In this study, we propose a freeform and cell‐friendly drop‐on‐demand bioprinting strategy for creating corneal stromal 3D models as suitable implants. Corneal stromal keratocytes (CSK) were bioprinted in collagen‐based bioinks as 3D biomimetic models and the geometrical outcome as well as the functionality of the bioprinted specimens were evaluated after in vitro culture. We showed that our bioprinting method is feasible to fabricate translucent corneal stromal equivalents with optical properties similar to native corneal stromal tissue, as proved by optical coherence tomography. Moreover, the bioprinted CSK were viable after the bioprinting process and maintained their native keratocyte phenotypes after 7 days in in vitro culture, as shown by immunocytochemistry. The proposed bioprinted human 3D corneal models can potentially be used clinically for patients with corneal stromal diseases.